(untitled) (Journal of Student Affairs in Africa, 2022)
The first year of higher education is one of the most critical and challenging times in a student’s life and choosing a specific course of study can be very difficult. Often, first-year students realize they have different expectations from the courses of study they chose and perceive that their abilities, skills, interests, and ambitions for a future career do not match their chosen courses of study. When the wrong choice has been made, and there is no intervention to choose a course with a more appropriate fit, students may decide to leave university prematurely, which may have a major impact on a student’s life. Identifying students who do not experience alignment with their choice of study course, and offering these students assistance and guidance, is imperative for universities to retain as many students as possible. Unfortunately, there is a paucity of research on a short scale that measures student-course fit validly and reliably, and which can be fairly applied to different groups in an unbiased manner. This study analyses the psychometric properties of a measure of students’ perceptions of fit with their course of study, adapted from a widely used person-job fit scale. Statistical techniques used to determine the validity and reliability of this scale were structural validity, differential item functioning to determine item bias, measurement invariance, and reliability. A quantitative, cross-sectional design was used. A sample (N = 1,211) of South African first-year university students studying at a university with three different campuses was used. As expected, confirmatory factor analysis provided evidence of a one-factor structure. No item bias was present for language and gender groups. Although item bias was present for item 2 between campuses, the post hoc analysis indicated that the impact was practically negligible. Measurement invariance was established, as well as good reliability of the scale. The findings of this study can contribute to knowledge concerning the valid, reliable and fair measurement of first-year students’ perceived fit with their courses of study. In addition, insights could assist universities in identifying students who need proper career guidance to better match with their chosen courses of study.